Analisis Sastra Siber Dan Peran Pembaca Dalam Hiperteks: Studi Terhadap Novel “Mariposa” Karya Luluk Hf Pada Aplikasi Memories Dan Cerpen “Platform Dua” Karya Slamet Thohari Di Webstie Magrib.Id - Chelly Juliani; Halwah Shahifah Al Madani; Putri Rahayu Nur Vaizah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The development of digital technology has given birth to cyber literature that offers a new form of interactivity between writers and readers through digital media. This study aims to examine the form of interactivity and reader participation in the novel